(3OjhGf CHj aQGS GdMeOGfjs - (3CHh aQGS , GdMGQK Hf SYjO Hf MeOGf GdJZdHj GdQHYj, CHhaQGS GdMeOGfj,J (B357 (3g` s ((3Ydj Hf efUhQ GdoSWjej s)
(3ChdgG (B:s
(3bO cGf HOQ GdJeGe oMrSfG hGdfGS aj MHg ShGA s
(3BNQgG (B:s
(3ef CQLhRI aj GdWQO(B: (3hde fRd SHY djGmd YOOG CSYnO nerf QGM hCSXi ef ZOG s
(3HChdgG JMHjS dCMeO GdefUhQ Ydi NRGfI GdbQhjjf SfI (B1011 (3ocJHJ HQSe NRGfI CMeO GdefUhQs
(3hQO CjVkG JMJ Qbe (B475s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B156s
Keywords: (3GdCOHs